Shell encapsulation of parasitic nematodes by Arianta arbustorum (Linnaeus, 1758) in the laboratory and in field collections. (18th December 2017) - Rae, Robbie
Abstract: There are 108 species of nematode that are known to have co-evolved with gastropods and use them as definitive, intermediate or paratenic hosts. One nematode ( Phasmarhabditis hermaphrodita ) is lethal to eight species of snail, but nine species are resistant for unknown reasons. This study investigated whether a previously untested snail species, Arianta arbustorum, was susceptible to P. hermaphrodita . Snails were exposed to 0, 30 and 90 P. hermaphrodita per cm 2 applied to the soil surface for 40 days. Survival, feeding inhibition and differences in weight were monitored. It was found that A. arbustorum was resistant to P. hermaphrodita. The nematode did not cause mortality, induce feeding inhibition or affect weight. At the end of the experiment, surviving A. arbustorum had encapsulated and killed the invading nematodes in their shells. Inspection of shells of A. arbustorum collected on sand dunes in the north of Scotland, and in those collected by others in 1966 and 1908, revealed the presence of encapsulated nematodes. Arianta arbustorum can encapsulate and kill invading nematodes under laboratory conditions and in the wild, and the evidence of encapsulation remains for a long time.